Regional Economic Integration and Income Inequality in Selected ASEAN Countries - Tan, Ger Ean; Shazali, Abu Mansor; Shirly Wong, Siew Ling (Human Resource Management Academic Research Society (HRMARS), 2020)
Widening income inequality in recent years has triggered an outpouring analysis and reflection on the causes of inequality. Economic cooperation demonstrated robust economic growth, reducing poverty but also accompanied by rising inequality. The income gap persists between ASEAN-5 (Indonesia, Malaysia, the Philippines, Singapore, Thailand) and the ASEAN-3 (Cambodia, Laos, Vietnam) has become a prominent issue and policy debate. Hence, this study aims to investigate the relationship of regional economic integration and income inequality by adopting a balanced panel analysis for selected ASEAN countries from 2005 to 2018. Trade and financial integration was evaluated to investigate the influence on inequality. Empirical findings showed that trade integration is more effective than financial integration in improving income distribution. Export activities from the manufacturing and service sectors help ASEAN-5, while the agricultural and manufacturing sectors help ASEAN-3 in narrowing income distribution. Therefore, integration policies to improve inequality should not be universally implied on countries with diverse economics structures and varied development activities